GIS-SUPPORTED CHARACTERIZATION AND GEOGRAPHICAL TARGETING INTERVENTIONS IN PROJECT DISPLACED COMMUNITIES IN DUTSE, NIGERIA - Oyedepo, John A.; Oloruntoba, O.; Oyedepo, E. O. (FUDMA JOURNAL OF SCIENCES, 2022)
The establishment of Federal University Dutse led to the displacement of some villages in the project site. The post construction impacts on these communities require urgent directing of interventions. The study analyzed the social problems associated with Communities’ displacement and employed geospatial techniques in geographical targeting of interventions in Dutse Jigawa State Nigeria. Results of the analysis show that almost all communities are deprived of essential amenities including good roads, elementary schools, pipe borne water, primary health care, telecommunication and farmlands. Spatial analysis gave insight to the relative needs and level of poverty amongst the displaced rural communities in Dutse. The facilities and the most central locations for them namely: Gurungu, Maidobi and Hausawa were easily determined from the geospatial analysis. The study found GIS mapping very useful in revealing the relative magnitude of social challenges and the intervention needs among project affected communities.